PENGARUH LINGKUNGAN KERJA, KARAKTER INDIVIDU DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA KARYAWAN PANEN PADA PT. SERBA HUTA JAYA - Kurniawati, Fitri; Nurjanah, Danik; Hanum, Tri Arfa (Lampung University, 2025)
This study aims to describe and explain the influence of work environment, individual characteristics, and job characteristics of a company on employee performance. The type of research used in this thesis is descriptive with a qualitative approach. The study was conducted at PT. Serba Huta Jaya. The sample in this study consisted of harvest employees at PT. Serba Huta Jaya, totaling 30 employees. The data analysis technique used is multiple linear regression analysis. Data obtained from measurements using the Likert scale were qualitatively collected and then quantified using ordinal measurements. The results of this study indicate that the work environment, individual characteristics, and job characteristics have an effect on the performance of harvest employees at PT. Serba Huta Jaya. This means that when the work environment, individual characteristics, and job characteristics function well together, they will improve the performance of the harvest employees at PT. Serba Huta Jaya. Keywords: job characteristics, individual characteristics, work environment